Review of "Ɓarawa lexicon: a wordlist of eight South Bauchi (West Chadic) languages: Boghom, Buli, Dott, Geji, Sayanci and Zul" by Ronald Cosper, Munich: LINCOM EUROPA, 1999 - (:unkn) unknown (My University, 2002)
Review of a wordlist of 8 south-Bauchi Chadic languages spoken in northern Nigeria
Keywords: African Research